2013
DOI: 10.1177/1076029613475474
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–Lymphocyte Ratio and the Platelet–Lymphocyte Ratio Predict the Limb Survival in Critical Limb Ischemia

Abstract: Admission NLR and PLR both merit further evaluation as prognostic indices in patients with CLI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 32 publications
2
64
0
Order By: Relevance
“…Gary et al proved that an increased PLR is significantly associated with patients at high risk for critical limb ischemia (CLI) and other cardiovascular endpoints [8]. By means of NLR and PLR CLI patients with a high risk for limb amputation during a five-year follow-up period were discriminated from patients with a lower risk for limb amputation during the same follow-up period [25]. NLR and PLR can be easily calculated as the neutrophils-tolymphocytes ratio and platelets-to-lymphocytes ratio in the peripheral blood and practical, inexpensive, and also valuable as high-cost inflammatory markers including IL-6, IL-1b, IL-8, and TNF-alpha.…”
Section: Discussionmentioning
confidence: 99%
“…Gary et al proved that an increased PLR is significantly associated with patients at high risk for critical limb ischemia (CLI) and other cardiovascular endpoints [8]. By means of NLR and PLR CLI patients with a high risk for limb amputation during a five-year follow-up period were discriminated from patients with a lower risk for limb amputation during the same follow-up period [25]. NLR and PLR can be easily calculated as the neutrophils-tolymphocytes ratio and platelets-to-lymphocytes ratio in the peripheral blood and practical, inexpensive, and also valuable as high-cost inflammatory markers including IL-6, IL-1b, IL-8, and TNF-alpha.…”
Section: Discussionmentioning
confidence: 99%
“…An increased PLR is associated with critical limb ischemia and vascular diseases such as atherosclerosis [15] . Durmuş et al [12] and Seo et al [6] observed that the PLR was significantly higher in adult patients with ISHL than in those in the healthy group.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil and lymphocyte counts can be obtained from the leukocyte number in the complete blood count. NLR is considered a marker of inflammation and it is suggested that NLR has prognostic significance in some systemic disorders [7,8,19]. NLR is important as it provides information regarding two different pathways: 1) neutrophils resulting from ongoing inflammation; 2) lymphocytes in the regulatory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophillymphocyte ratio (NLR) is a marker that can be estimated by using leukocyte subtypes from the complete blood count. Moreover, it has been reported that NLR may have prognostic value in some diseases [7,8].In the current literature, there is no study evaluating MPV and NLR together in gout. In this retrospective study, we investigated the role of MPV and NLR in the determining disease activity in gout disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation